First report of the reproduction in captivity of the Chocoan Bushmaster, Lachesis acrochorda (García, 1896) (2015)
ABSTRACT: The Serpentarium at the Universidad de Antioquia houses four specimens of the Chocoan bushmaster (Lachesis acrochorda) in a vivarium simulating natural habitat conditions. After an acclimatization period of nine months the moisture level in the enclosure was increased artificially to induce reproductive behaviour. One male was observed to court a female for 15 days, but copulation was not observed. The female subsequently refused food and 110 days after the last observation of courting 11 eggs (average weight 57.9 g) were discovered. While three eggs were artificially incubated, the rest were left in the vivarium; both sites were monitored continuously. On Day 74 of incubation, the eggs in the vivarium were moved to an incubator due to a drop in temperature. Hatching began on Day 93 and seven eggs hatched during a 3-day period. Average weight (42.0 ± 3.6 g) and length (40.0 ± 1.4 cm) of the neonates was recorded. This is the first report of captive reproduction for L. acrochorda.